2006
DOI: 10.1093/europace/euj024
|View full text |Cite
|
Sign up to set email alerts
|

Use of a new cardiac pacing mode designed to eliminate unnecessary ventricular pacing

Abstract: AAIsafeR2 mode seems to be safe and reliable in patients with infrequent slowing or pauses in ventricular activity, while maintaining ventricular pacing below 1%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 28 publications
0
23
0
1
Order By: Relevance
“…Therefore, various pacing modes were developed in recent years to favor spontaneous AV conduction. The SafeR™ pacing mode (SORIN Group CRM SAS, Clamart, France), designed to combine the advantages of AAI with the safety of DDD mode, has been described in detail elsewhere 13,14 . The first recently published clinical application of SafeR in selected pacemaker recipients showed that it was associated with a marked decrease in the percentage of ventricular paced events.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, various pacing modes were developed in recent years to favor spontaneous AV conduction. The SafeR™ pacing mode (SORIN Group CRM SAS, Clamart, France), designed to combine the advantages of AAI with the safety of DDD mode, has been described in detail elsewhere 13,14 . The first recently published clinical application of SafeR in selected pacemaker recipients showed that it was associated with a marked decrease in the percentage of ventricular paced events.…”
Section: Introductionmentioning
confidence: 99%
“…In that case pacing was permanently reprogrammed to DDD. The upgraded AAIsafeR version 2 has been incorporated in the Symphony™ DR 2550 pacemaker (ELA Medical, Montrouge, France) since March 2005, with a view to remedy this deficiency by systematically switching to AAI every morning, and by improving the management of first‐degree AV block 17 . At night, when vagal tone slows AV conduction, AAIsafeR intends to prevent ventricular pacing, with minimal hemodynamic consequences, as long as the heart rate is preserved.…”
Section: Introductionmentioning
confidence: 99%
“…All patients enrolled in the trial received a Symphony DR 2550 cardiac pacemaker (SORIN CRM SAS, Clamart, France) equipped with the SafeR algorithm. Details of this algorithm have been previously described . In summary, SafeR provides AAI(R) pacing while continuously monitoring AV conduction and reverts to DDD(R) pacing when required for AV block of any degree.…”
Section: Methodsmentioning
confidence: 99%
“…The SafeR algorithm (Sorin CRM, Clamart, France) was developed to provide a pacing mode that combines the benefits of AAI with the safety of DDD pacing . The recent randomized SaveR study confirmed the superiority of SafeR in reducing RV pacing when compared to standard DDD pacing in selected patients without high‐degree AV block and in a more general pacemaker population.…”
Section: Introductionmentioning
confidence: 99%